An analytical model for the rotational behavior of concrete segmental joints with gaskets. Issue 13 (October 2019) - Yang, Fan; Cao, Shengrong; Li, Qingbin
To investigate the rotational behavior of concrete segmental joints with gaskets, bending tests are performed by detailed three-dimensional continuum numerical models for joints with and without gaskets. Based on the numerical results, an analytical model is proposed to analyze the rotational stiffness of the segmental joint and extend the simulation with related parametric studies. The bending tests reveal that the rotational behavior of the segmental joint with gaskets can be divided into four stages for both the sagging and hogging moment cases. The analytical results reveal that the sealing gasket has little inﬂuence on the joint rotational behavior, while the elastic gasket has a significant effect of reducing the joint rotational stiffness. Besides, the rotational behavior of the joint with gaskets is affected by the axial force and the bolt pre-tightening force to a certain degree. The proposed analytical model allows the effect of the properties of bolts and various gaskets, the concrete contact force, the geometry of the joint section, and the subjected loads to be taken into consideration. The analytical results are well consistent with the numerical results, and the analytical model can be adopted for simulation of the segmental joint with various gaskets.